Wastewater treatment efficiency in stabilization ponds, Olang treatment plant, Mashhad, 2011-13 - Hadi Rahmatiyar; Elham Rahmanpour Salmani; Mohammad Reza Alipour; Hossein Alidadi; Roya peiravi (Iranian Journal of Health, Safety and Environment, 2015)
Olang wastewater treatment facilities purifying raw urban wastewater consist of two stabilization pond modules. Both are on operation in parallel. Functioning of natural systems is influenced by different factors including ambient condition. Considering final effluent of this system discharges to Kashafrood river and sometimes is used for agricultural purposes, assessing the quality parameters in effluent was the main objective of this study. This cross-sectional study investigated some important quality parameters for both raw and treated wastewater in two years periods. Data analysis was carried out using descriptive statistics. Statistical tests were done at a significant level of 0.05. Simple linear regression analysis was used only for modeling. Raw wastewater was almost severe. Average removal efficiency for BOD5, COD, and TSS was 81, 83, and 78% respectively. There wasn't a meaningful relationship between the removal efficiency of mentioned parameters and input pH. Ambient temperature fluctuations were effective on BOD5, and COD reduction. SAR index didn't show a considerable restriction on irrigation application of effluent. In 62.5% cases outlet Na content was at the extent to which restrictions were imposed. Olang wastewater treatment plant generates an acceptable effluent relating to most of the quality parameters that were measured in this study. Considering special status of Mashhad city, it is worthy to reuse effluent in areas with a high water requirement such as agriculture.